J. Dybiec, Uniwersytet Jagielloński (1918-1939), Kraków 2000, ss. 759 - Szulakiewicz, Władysława (Biuletyn Historii Wychowania, 2000)
J. Dybiec, Uniwersytet Jagielloński (1918-1939), Kraków 2000, ss. 759